Modelo de dinámica de sistemas para optimizar el proceso de atención en el comedor universitario de la Universidad Nacional de la Amazonía Peruana - Jimenez Huisa, Denis (2023)
This study focused on the optimization of the service process in the university canteen of the National University of the Peruvian Amazon (UNAP). The main objective was to develop a system dynamics model that would improve service efficiency and reduce waiting times, thus improving customer satisfaction and the performance of dining room staff. To achieve this objective, an applicative-projective research methodology was used, with a quantitative approach and non-experimental design. The population consisted of 288 diners university students with a sample of 68. The data was collected through direct observation and surveys, and processed with statistical techniques and the system dynamics model. The results indicated that the implementation of the system dynamics model made it possible to identify and consider all the relevant variables that influence the service process in the university canteen. This made it possible to improve the efficiency of the service, reduce waiting times and increase customer satisfaction. The evaluation of the model also demonstrated its ability to optimize the service process and provide shorter wait times and better management of diner flow compared to current dining room performance data. In conclusion, the implementation of the system dynamics model was effective in optimizing the service process in the university canteen of the National University of the Peruvian Amazon.